Parosteal Chondrolipoma of the Scapula: A Case Report - Yeon Jang; Ji Young Yoo; Joon Seog Kong (Journal of the Korean Society of Radiology, 2024)
Parosteal lipoma is a rare tumor that occurs very close to the bone, and accounts for approximately 0.3% of all lipomas. Chondrolipoma, a lipoma with cartilaginous metaplasia, is also a rare tumor consisting of mature adipose and cartilage tissues. Therefore, a tumor with characteristics of both parosteal lipoma and chondrolipoma simultaneously is extremely rare. Herein, we report the imaging findings of a parosteal chondrolipoma arising in the right periscapular area, confirmed based on surgical resection and histopathologic examination.